Associations Between Cessation of Second-Line Therapies and Relapse Rates of Childhood Refractory Minimal-Change Nephrotic Syndrome: A Single-Center, Retrospective Chart Review - Jing Jin, MSc; Yufeng Li, MD, PhD; Yaju Zhu, MSc; Jiajia Ni, MD, PhD (Elsevier, 2022)
ABSTRACT: Background: Most patients (≥85%) with minimal-change nephrotic syndrome (MCNS) respond to corticosteroid treatment. However, about 10% to 20% of patients with MCNS have steroid-resistant nephrotic syndrome and 25% to 43% of patients have steroid-dependent nephrotic syndrome or frequent-relapse steroid-sensitive nephrotic syndrome. Patients with refractory MCNS are treated with various second-line therapies. Objectives: This study aimed to evaluate the associations between the use of various second-line therapies and relapse rates in Chinese patients with childhood refractory MCNS. Methods: In this study, patients with childhood nephrotic syndrome renal biopsy proved to be "minimal change" from a single tertiary-care center between January 2002 and July 2018 were identified. A Total of 56 medical charts of patients treated with 1 of these second-line immunosuppressors: cyclophosphamide (CYC), mycophenolate mofetil (MMF), or tacrolimus (TAC) were reviewed. Patients were divided into CYC (n = 24), MMF (n = 20), and TAC (n = 12) groups according to the second-line therapy administered. Baseline characteristics, immune status, immunocomplex deposition in the renal tissue, and treatment outcomes were analyzed. Results: The ratio of patients with steroid-resistant nephrotic syndrome and steroid-dependent nephrotic syndrome in the CYC, MMF, and TAC groups did not differ significantly (P = 0.721). The immunofluorescence assay did not show any significant differences in immunocomplex deposition identified in renal biopsy specimens among the 3 groups. The rate of steroid-free remission in the TAC group (75%) was higher than that in the MMF (55%) and CYC (25%) groups (P = 0.012). At the last follow-up, two-thirds of children in the TAC group had a relapse following discontinuation of therapy. In the TAC group, patients for whom steroids were withdrawn had significantly higher levels of immunoglobulin G at the onset of nephrotic syndrome than those for whom steroids were continued (P = 0.017). In the MMF group, children with relapse had a significantly higher percentage of CD16+CD56+-positive cells than those without relapse (P = 0.042). The relapse rate after treatment discontinuation was significantly different among the 3 groups (P = 0.035). Notably, the relapse rate after treatment discontinuation in the CYC group was lower than those in the other 2 groups (P = 0.035). Conclusions: In this small population of Chinese patients with childhood refractory MCNS, the relapse rate following TAC therapy was higher than that following MMF or CYC therapy. Different proportions of CD16+CD56+-positive cells might be associated with relapse rates in patients with MCNS receiving MMF treatment. (Curr Ther Res Clin Exp. 2022; 83:XXX-XXX)